HUBUNGAN HUKUM PARA PIHAK DALAM PRINSIP MUDARABAH MENURUT HUKUM PERDATA DI INDONESIA - Wahid Hadi Purnomo (Maliyah : Jurnal Hukum Bisnis Islam, 2014)
Islamic banking is a banking system that is relatively new in Indonesia. Islamic banking is expected to be one of the alternatives to restore public confidence in the post-crisis conventional banking and diversified financial risk of creating more diverse so as to enhance the resilience of the national banking system. Therefore, the Islamic banking system is still new, there permaslahan-problems arising as a response to Islamic banks, the construction of which is how the legal relationship of the parties, the responsibility of the bank as the owner of the funds and the customer receiving financing as fund manager when there is a loss in cooperation mud}a>rabah. In the known Islamic Sharia principles, which principles derived from the Qur'an and Hadith as well as be used as guidelines by Islamic banks in conducting business activities that do not include an element of riba>, maisi>r, ghara>r, hara>m and z}a>lim. This is what distinguishes the conventional banks, one of which is mudarabah. The difference between the principles of conventional banks and Islamic banks on the basis of mud} a> Rabah lead to differences in the legal relationship with the bank's customers and different legal responsibilities on both banks.